2020
DOI: 10.1016/j.marpolbul.2020.111066
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diagenesis of trace metals in marine sediments of a coastal Mediterranean area: St Georges Bay (Lebanon)

Abstract: St-Georges Bay (Lebanon) is an open bay, to the Mediterranean Sea and it is exposed to numerous anthropogenic activities such as industrial effluents, non-treated wastewater discharge and maritime activities leading an increasing chemical contamination especially with trace metals. Contamination with trace metals (Cu, Cd, Co, Pb, As, Ag and Hg) and the influence of early diagenesis on their distribution are studied on both sediments and waters transect. For this purpose, sediment cores were collected, then tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 53 publications
(93 reference statements)
1
1
0
Order By: Relevance
“…The concentrations of As in Baltic Sea sediment porewater are comparable with our results, whereas V is even higher (van de Velde et al, 2020;Scholz and Neumann, 2007). The two studies in Mediterranean sediment porewaters present the lowest element concentrations for the European regions (EI Houssainy et al, 2020;Dang et al, 2015), while the study in Great South Bay, USA, indicates relatively high Ni and V concentrations (Beck et al, 2010), which is comparable to our results. But other element concentrations are much lower than in this study.…”
Section: O R R E C T E D P R O O Fsupporting
confidence: 90%
“…The concentrations of As in Baltic Sea sediment porewater are comparable with our results, whereas V is even higher (van de Velde et al, 2020;Scholz and Neumann, 2007). The two studies in Mediterranean sediment porewaters present the lowest element concentrations for the European regions (EI Houssainy et al, 2020;Dang et al, 2015), while the study in Great South Bay, USA, indicates relatively high Ni and V concentrations (Beck et al, 2010), which is comparable to our results. But other element concentrations are much lower than in this study.…”
Section: O R R E C T E D P R O O Fsupporting
confidence: 90%
“…Chemical speciation analysis using the sequential extraction method indicated that except for Cd and Cu, all other heavy metals had a large fraction associated with Fe/Mn oxides (F3) for both river-bed and river-side sediments (Figure ). This phenomenon was attributed to the strong adsorption capacity of Fe/Mn oxides for heavy metals, , and potential incorporation of heavy metals into Fe/Mn mineral structures. ,, The operationally defined Fe/Mn fraction also included the heavy metals associated with sulfides because metal sulfides would dissolve and release heavy metals during the extraction process . TEM analysis was tried to reveal the physical associations of the heavy metals with Fe/Mn and S. The low concentrations of the heavy metals in the sediment samples, however, prevented unambiguous identification of such associations.…”
Section: Results and Discussionmentioning
confidence: 99%